Natural Alternatives and Therapeutic Approaches for Managing Cholestatic Pruritus: A Comprehensive Review - Kumar BS, Ashok (Journal of Neonatal Surgery, 2025)
Cholestatic pruritus is a debilitating condition commonly associated with liver diseases such as primary biliary cholangitis, primary sclerosing cholangitis, and cirrhosis. It significantly impacts the quality of life, and current treatments often offer limited efficacy and are associated with adverse side effects. This review explores natural alternatives for the management of cholestatic pruritus, focusing on medicinal plants and herbs with potential therapeutic effects. We specifically examine Gardenia jasminoides, Citrus aurantium, Artemisia capillaris, Rehmannia glutinosa,Lycium barbarum, Andrographis paniculata, Picrorhiza kurroa, Rheum officinale,Glycyrrhiza glabra, Solanum nigrum, Radix Isatidis, Ziziphus jujube, which have demonstrated anti-inflammatory, hepatoprotective, and pruritus-relieving properties. These plants contain a variety of bioactive compounds such as flavonoids, saponins, alkaloids, and terpenoids, which have been shown to modulate bile acid metabolism, reduce oxidative stress, and alleviate inflammation. Clinical and preclinical studies support the therapeutic potential of these plants, with many showing significant improvements in pruritus severity, liver function, and overall patient well-being. Moreover, these natural remedies offer an alternative to conventional therapies, often with fewer side effects. The review highlights the need for further research to understand the mechanisms of action of these plants, optimize their therapeutic efficacy, and establish standardized treatment protocols. The promising results from traditional medicine and phytotherapy open new avenues for the development of safer, more effective treatments for cholestatic pruritus.